Degradação do cabelo humano causada pelo uso de alisantes contemporâneos e outros processos químicos - Colenci, Ana Vivian Parrelli (2017)
In the XXI century, there has been an increasing research on cosmetic agents including chemical changes. Consequently, new smoothers have come up, such as: carbocisteine, glyoxylic acid and the forbidden formaldehyde. Ammonium thioglycolate is classified as a classic smoother and the smoothing products such as glyoxylic acid, carbocisteine and formaldehyde are considered as contemporary smoothers. Scientific studies that address the mechanism, action of the contemporary smoothers are scarce, and few of them approach the impact of those substances on the hair fiber. Those smoothers have been generating a capillary structure with different chemical, physical and structural characteristics. These changed molecular / atomic characteristics are still largely unknown. Thus, this study analyses the effects of the smoothers containing glyoxylic acid, carbocisteine, formaldehyde and ammonium thioglycolate in cases of one application and successive applications, and concomitantly with other chemical processes such as staining and discoloration of the hair fiber. Mechanisms of the glyoxylic acid, carbocisteine and formaldehyde were presented. Techniques such as fluorescence spectroscopy, electron microscopy of field emission and mechanical resistance have been applied. The aim was a better understanding of the diverse types of damages on the hair fibers caused by the studied smoothers. In addition to it, the staining and discoloration processes were analysed together the action of the smoothers from the macro and microscopic standpoints.